Metal Extractability Changes in Soils Under Thorny Amaranth - Salam, Abdul Kadir; Novpriansyah, Hery; Bucharie, Henrie (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2022)
The different forms of heavy metals may be significantly extracted from soils by plant roots. In a glasshouse experiment, the shifting of soil heavy metal forms under thorny amaranth was examined. To accomplish the research goal, thorny amaranth was planted for four weeks at field water content in soils with varying Cu and Zn contents. Copper and Zn levels in the soil were measured both before and after planting. High soil Cu and Zn levels reduced this plant's height and dry biomasses. Thorny amaranth considerably reduced the exchangeable and available Cu and Zn in the soil. The soil exchangeable and available Cu and Zn had a good correlation with the plant uptakes of these elements. Copper and Zn reductions by planting significantly lower than the available Cu and Zn. A significant portion of the soil exchangeable Cu and Zn shifted to stronger bonding during the incubation time. It was demonstrated that plants absorbed more Cu and Zn from forms different than the soil-exchangeable forms.